Case Report: From diagnosis to therapy: a lung ultrasound-driven precision strategy for neonatal atelectasis management - Chen, Qi; Xiong, Wei; Jun, Li (Frontiers in Pediatrics, 2025)
ObjectiveTo examine the clinical value of lung ultrasound (LUS) in the individualized management of neonatal atelectasis and assess its effectiveness in directing condition-specific treatment strategies.MethodsThree neonatal atelectasis cases with differing causes, pneumonia, pulmonary hemorrhage, and meconium aspiration syndrome, were treated with LUS-guided, personalized interventions. These included ultrasound-directed airway clearance, selective bronchoalveolar lavage, and high-frequency chest wall oscillation.ResultsLUS enabled continuous, real-time assessment of atelectasis severity and distinct pathological signs such as hepatization and the shred sign. This imaging guidance allowed targeted therapies that shortened hospitalization by an average of 40%. In all cases, lung re-expansion was achieved without adverse events.ConclusionDue to its lack of radiation, high sensitivity, and real-time feedback, LUS offers a valuable tool for guiding individualized, etiology-specific therapies in neonatal atelectasis. It presents a clinically adaptable approach for optimizing outcomes in this population.